G283(P) Impact of adversity on early childhood growth & development in rural india: findings from the spring cluster-randomised controlled trial. (May 2019) - Bhopal, S; Roy, R; Verma, D; Kumar, D; Khan, B; Soremekun, S; Divan, G; Kirkwood, B
Abstract : Background and aims: Improving early childhood development globally will lead to improved health and wellbeing for all and is key to achieving the ambitious Sustainable Development Goals. Exposure to a cumulative burden of adversity is detrimental to child health and wellbeing across the lifecourse, but the relative importance of the very early years is less well known. We therefore examined the contribution of multiple adversities to impaired growth and development in young infants in rural India. Methods: We enrolled pregnant women and newborns from all households across 120 villages in rural Haryana, India. We assessed 22 adversities in the first year of life across four domains: socioeconomic, maternal stress, family-child relationship, and child. We measured child weight and length and did Bayley Scales of Infant Development-III (BSID-III) outcome assessments when children reached 18 months of age. We used multiple linear regression techniques to assess the relationship between cumulative adversity and outcomes. Results: We assessed 1273 children. 42% had four or more adversities. We found consistent and strong negative relationships between cumulative adversity and growth and development outcomes. Decrease in BSID-III scores for each adversity was −1.1 (95% CI −1.3, −0.9) for motor, −0.8 (95% CI −1.0, −0.6) for cognitive, −1.4 (95% CI −1.8, −1.1) for language scale. Similarly for height-for-age the decrease was −0.12 (95% CI −0.14, −0.09) and for weight-for-age −0.09 (95% CI −0.11, −0.06) z-scores (table 1 ). Change in the mean scores for zero versus 8+adversities was 10.3 points for motor, 7.8 points for cognitive, 11.5 points for language, 1.12 z-scores for length and 0.95 z-scores for weight. Conclusions: Childhood adversity poses a considerable burden for lifelong health and wellbeing, even in the very youngest children. Urgent intervention is required to support families and communities to allow all children to reach their development potential.